2023
DOI: 10.1108/josm-03-2022-0090
|View full text |Cite
|
Sign up to set email alerts
|

How does service robot anthropomorphism affect human co-workers?

Abstract: PurposeService robots are gradually becoming more anthropomorphic and intelligent. This research aims to investigate how anthropomorphic service robots with different levels of intelligence affect their human counterparts.Design/methodology/approachTwo between-subject experimental studies were used to test whether different levels of service robot anthropomorphism with different levels of intelligence influence employees' morale and resistance to service robots.FindingsStudy 1 shows that the effect of service … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(1 citation statement)
references
References 67 publications
(156 reference statements)
0
1
0
Order By: Relevance
“…That is why credibility is an important determinant for the effectiveness of brand use of VIs. By anthropomorphizing brands with personalities and human attributes, marketers have made them more relatable to consumers (Golossenko et al, 2020; Tojib et al, 2023; Wen Wan et al, 2017). In fact, Sundar (2004) and Kim and Sundar (2012) both found that consumers exposed to a human‐like agent perceive the information as more credible than those not exposed to a human‐like agent.…”
Section: Conceptual and Theoretical Model Research Model And Literatu...mentioning
confidence: 99%
“…That is why credibility is an important determinant for the effectiveness of brand use of VIs. By anthropomorphizing brands with personalities and human attributes, marketers have made them more relatable to consumers (Golossenko et al, 2020; Tojib et al, 2023; Wen Wan et al, 2017). In fact, Sundar (2004) and Kim and Sundar (2012) both found that consumers exposed to a human‐like agent perceive the information as more credible than those not exposed to a human‐like agent.…”
Section: Conceptual and Theoretical Model Research Model And Literatu...mentioning
confidence: 99%